Utilization and development of Smart Mosque Applications - Febrianty, Febrianty; Thantawi, Ahmad Muhammad; Budilaksono, Sularso; Anwar, Nizirwan; Komsiah, Siti (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Mosque is pointing to a place (building) whose main function is as a place of prostration and worship of Allah SWT. Mosque digitization is one form of mosque adaptation to technological developments towards digital. This of course will be able to improve the service of the mosque to the congregation. However, many mosques have not moved towards digitization. A system for managing data and information, such as: mosque activities, congregational data, financial reports, and so on. Currently, there are quite a lot of user acceptance model theories for an application. One of them is the model of user satisfaction. Data collection is done by using a survey of user satisfaction with the application. The methods used in research in the development and implementation of networks and digitalization in terms of questions and answers to interviews with several mosque DKM administrators by the development team are: at the Nurul Hidayah mosque, Al Ikhlas Pademangan mosque, Attaqwa Grand Mosque, Asy Syam Mosque, Jami Al Manar Mosque, Jami Al-Hidayah Mosque, Baitussalam Mosque (Bogor), and Al-Ikhlas Mosque, all of which are still in the Jakarta area. As well as the results of the questionnaire that was made, there were Questionnaire Results of the System Usability Scale (SUS) Testing for the Smart Masjid application regarding customer satisfaction, which was carried out by survey research through a questionnaire form and interview. The results of the average answer to the questions given are 80% - 85% Answering Agree and Strongly Agree, the rest only partially answered Doubtful and Disagree.